1992
DOI: 10.1161/01.res.71.2.357
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous calcitonin gene-related peptide mediates nonadrenergic noncholinergic depressor response to spinal cord stimulation in the pithed rat.

Abstract: The role of endogenous calcitonin gene-related peptide (CGRP) in the nonadrenergic noncholinergic depressor response to spinal cord stimulation was studied in the pithed rat in vivo. Pithed rats were given hexamethonium (2 mg/kg per minute i.v.) to block autonomic outflow, and mean blood pressure was artificially maintained at approximately 100 mm Hg with methoxamine (10-15 micrograms/kg per minute i.v.). Electrical stimulation of the spinal cord at the level of the lower thoracic vertebra (T9-12) caused a fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 30 publications
7
72
1
Order By: Relevance
“…Furthermore, the augmented pressor response was more pronounced for SCS than for exogenously applied NA. In pithed rats, pressor responses to SCS have been shown to be mediated by activation of sympathetic adrenergic nerves, since an adrenergic neuron blocker (guanethidine) and autonomic ganglionic blocker (hexamethonium) abolished the response (13,16). Therefore, it is very likely that sympathetic nerve activity is augmented in the chronic hyperinsulinemic state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the augmented pressor response was more pronounced for SCS than for exogenously applied NA. In pithed rats, pressor responses to SCS have been shown to be mediated by activation of sympathetic adrenergic nerves, since an adrenergic neuron blocker (guanethidine) and autonomic ganglionic blocker (hexamethonium) abolished the response (13,16). Therefore, it is very likely that sympathetic nerve activity is augmented in the chronic hyperinsulinemic state.…”
Section: Discussionmentioning
confidence: 99%
“…After the trachea was cannulated, the animals were pithed by inserting a stainless-steel rod (1.4 mm in diameter) through the right orbit and the foramen magnum and down into the spinal cord to the level of the sacral end, and then the tip of the rod was raised to the thoracolumbar vertebrae (Th 9-12) according to the method described previously (16,17). Artificial respiration (4.5 ml/breaths/kg, 70 breaths/min) with room air was immediately started using an artificial respirator (model 683; Harvard Apparatus, South Natic, USA).…”
Section: Pithing and Measurementmentioning
confidence: 99%
“…It, therefore, raises the question how the sensory nerve is able to participate in the regulation of resistance vessel tone similar to the adrenergic efferent nerve. This question was resolved by the in vivo study of Taguchi et al (19) with the pithed rat in which blood pressure was artificially elevated by methoxamine in the presence of hexamethonium, an autonomic ganglion blocker. The findings of that study showed that electrical stimulation of lower thoracic spinal cord (Th9 -12) but not upper thoracic cord (Th1 -4) caused a frequency-dependent fall in blood pressure without changing heart rate.…”
Section: Physiological Role Of Cgrpergic Nerves In the Regulation Of mentioning
confidence: 99%
“…In pithed animals, there is no intrinsic sympathetic nerve activity or centrally mediated compensatory reflex (Gray et al, 1990). The depressor response during spinal cord stimulation in the pithed rat is attributed to endogenous CGRP released from CGRPcontaining nerves (Taguchi et al, 1992). Volatile anesthetics inhibit NANC depressor responses through inhibition of the CGRP depressor effect, not through inhibition of CGRP release after NANC nerve stimulation in the pithed rat model (Yoshikawa et al, 2003), suggesting that volatile anesthetics inhibit vascular responses to CGRP.…”
mentioning
confidence: 99%